Co-Production in the ASSiK Programme: Enhancing Youth Work Readiness in Surabaya - Edista Indiswari Artamefia; Diana Hertati (UNIVERSITAS PAKUAN, 2026)
Youth unemployment remains a significant labour market challenge faced by the Surabaya City Department of Industry and Manpower. In response to this issue, the Surabaya City Government developed the ASSiK Programme (Arek Suroboyo Siap Kerjo), a digital-based public service innovation designed to connect job seekers with vocational training, employment opportunities, and industry partners. This study examines the implementation of co-production within the ASSiK Programme through four stages: co-commissioning, co-designing, co-delivery, and co-assessment. A qualitative descriptive approach was employed using interviews, observation, and documentation as data collection techniques. The findings demonstrate that the implementation of co-production in the ASSiK Programme involves collaboration among government institutions, private-sector actors, and youth participants in the planning, design, implementation, and evaluation of employment services. The programme has contributed to improving youth work readiness through vocational training, internship opportunities, and easier access to employment information. Although stakeholder participation has been evident throughout the programme, community involvement remains relatively limited and continues to be largely dominated by government institutions and industry actors.